Role of procalcitonin in diagnosis of community acquired pneumonia in Children - Vinod H. Ratageri; Puspha Panigatti; Aparna Mukherjee; Rashmi R. Das; Jagdish Prasad Goyal; Javeed Iqbal Bhat; Bhadresh Vyas; Rakesh Lodha; Deepak Singhal; Prawin Kumar; Kuldeep Singh; Samarendra Mahapatro; et al. (BMC, 2022)
Abstract Background The role of serum Procalcitonin (PCT) in adults in diagnosis of Community acquired pneumonia (CAP) is well established, however, role in pediatric CAP remains controversial. Objectives The objective of this study was to investigate the utility of serum procalcitonin in differentiating bacterial community-acquired lower respiratory tract infection from non-bacterial respiratory infection in children; radiologically confirmed pneumonia was used as the reference. In addition, we assessed the utility of adding the PCT assay to the clinical criteria for diagnosis of pneumonia. Study design Subanalysis of a larger prospective,multicentriccohort study. Participants Children, 2 months to 59 months of age, attending paediatric OPD of 5 urban tertiary care hospitals, suffering from acute respiratory infection (ARI). Intervention Detailed clinical history and examination findings of enrolled children were recorded on predesigned case record form. Samples for PCT were obtained at admission and were measured centrally at the end of the study except for one site using VIDAS® B.R.A.H.M.S PCT kit (Biomerieux SA, France). Outcomes Sensitivity and specificity of procalcitonin for diagnosis of radiologically confirmed pneumonia. Results Serum Procalcitonin was measured in 370 patients; median (IQR) age of these children being 12 (7, 22) months, 235 (63.5%) were boys. The median (IQR) serum procalcitonin concentration was 0.1(0.05, 0.4) ng/mL.Sensitivity and specificity of raised PCT (> 0.5 ng/mL) for pneumonia as per any CXR abnormalities were 29.7% and87.5%,(P < 0.001) respectively. Raised PCT was also significantly associated with consolidation (34.5%,79.2%,P < 0.02)and pleural effusion(54.6%,79%,P < 001). Adding PCT to the existing clinical criteria of WHO did not improve the sensitivity for diagnosis of pneumonia. PCT was significantly higher in children with severe pneumonia. Conclusion Positive PCT (> 0.5 ng/mL) is significantly associated with radiographic pneumonia but not with pneumonia based on WHO criteria.However, it can act as a surrogate marker for severe pneumonia.